Peran Kecerdasan Organisasi dalam Pelayanan Publik: Studi Kasus Dinas Kependudukan dan Pencatatan Sipil (Disdukcapil) Kota Tangerang - Yuniar, Aulia; Kalam, Rifki Syahril; Nurfadhilah, Intan; Putri, Annisa; Mukhayrah, Mukhayrah; Kurniawan , Irvan Arif (Universitas Pahlawan Tuanku Tambusai, 2025)
In the development of current technological advances, quality public services are the hope of the wider community. This study aims to analyze the Role of Organizational Intelligence in Public Services which focuses on the Population and Civil Registration Service (Disdukcapil) of Tangerang City. This study uses a qualitative and descriptive approach with data collection techniques such as interviews, observations, and documentation. The results of the study indicate that organizational intelligence is the ability to adapt, collaborate, and utilize technology that is applied through digital-based service innovations. The services developed by Disdukcapil such as the Sobat Disdukcapil website platform and the Sobat AI feature have succeeded in increasing operational efficiency, facilitating public access, and reducing the workload that is done manually. However, challenges in its implementation still remain, especially in the gap in understanding technology, especially among the elderly and employees who are accustomed to manual systems, remain an obstacle. The theory used as a reference in this study uses the theory of Karl Albrecht (2003) which includes (1) strategic vision, (2) sense of togetherness (Shared Fate), (3) readiness to change (Appetite for Change), (4) alignment and conformity (Alignment and Congruence), and (5) knowledge deployment (Knowledge Deployment). By applying these dimensions, organizations can increase their capacity to survive, develop, and remain relevant amidst continuous change.